Revitalizing female fertility: platelet-rich plasma – hype or hope? - Serdarogullari, Munevver; Raad, Georges; Makieva, Sofia; Liperis, Georgios; Fraire-Zamora, Juan J.; Celik-Ozenci, Ciler (Reproductive biomedicine online, 2024)
Platelet-rich plasma (PRP) has gained popularity as an experimental tool in regenerative medicine, with potential applications in reproductive medicine. This review will assess the existing literature on the role of PRP in female fertility enhancement, focusing on ovarian rejuvenation and increased endometrial thickness. PRP is being explored as a treatment for recurrent implantation failure, primary ovarian insufficiency and poor ovarian response. While the influence of PRP on endometrial thickness and implantation success is postulated, its effectiveness remains the subject of debate due to protocol variability and unclear patient selection criteria. This narrative review includes 36 articles published before December 2022, and highlights the lack of comprehensive molecular studies examining the impact of PRP on reproductive capacity. This review underscores the importance of standardizing PRP preparation protocols in reproductive medicine. However, challenges persist, and there is a need for well-planned randomized controlled trials and a deeper understanding of the patient population that would gain the greatest benefit from PRP treatment. Clarifying these aspects is crucial to improve outcomes for low-prognosis patients undergoing assisted reproductive technology.